Workshop Mural Bertema Wayang Beber Bagi Siswa-Siswi Sma/ Smk/Ma Se Kabupaten Pacitan - Aji Wiyoko (Institut Seni Indonesia Surakarta, 2016)
Wayang beber is one of Indonesian culture which has noble values. Introducing visual forms even their shows into young generation is importance in preservation. One of methods to introducing wayang beber visual forms is by mural.Mural art is painting into the walls.Mural object has many purposes as its placed. Mural on hustle places is easy to be appreciated. Wayang beber as mural object, on hustle places, very interesting to be realized. Key words : wayang beber, mural